Negotiating decisions on aggressive cancer care at end-of-life between patients, family members, and physicians – A qualitative interview study - Haun, Markus W.; Wildenauer, Alina; Hartmann, Mechthild; Bleyel, Caroline; Becker, Nikolaus; Jäger, Dirk; Friederich, Hans-Christoph; Tönnies, Justus (Frontiers in Oncology, 2022)
Background: Patients with advanced cancer do receive increasingly aggressive end-of-life care (AOC), despite it does often not prolong survival time but entails decreased quality of life for patients. This qualitative study explores the unfolding of AOC in clinical practice focusing on the decision-making process and the quality of end-of-life care from family members’ perspective. Materials and methods: We conducted semi-structured interviews with 16 family members (six family members of advanced cancer patients with AOC and ten without AOC) at the National Center for Tumor Diseases Heidelberg, Germany. We conducted a content analysis applying a theoretical framework to differentiate between ‘decision-making’ (process of deciding for one choice among many options) and ‘decision-taking’ (acting upon this choice). Results: While patients of the AOC group tended to make and take decisions with their family members and physicians, patients of the non-AOC group took the decision against more aggressive treatment alone. Main reason for the decision in favor of AOC was the wish to spend more time with loved ones. Patients took decisions against AOC given the rapid decline in physical health and to spare loved ones difficult decisions and arising feelings of guilt and self-reproach. Conclusion: Treatment decisions at end-of-life are always individual. Nevertheless, treatment courses with AOC and those without differ markedly. To account for a longitudinal perspective on the interplay between patients, family members, and physicians negotiating decisions on AOC, cohort studies are needed. Meanwhile, clinicians should validate patients and family members who consider refraining from AOC and explore their motives.